Investigation of the Inhomogeneity Phenomenon in the Metal/Semiconductor Interface: Mo/n-type-4H-SiC Schottky Diode - S. Toumi (Fundamental Research and Application of Physical Science Vol. 6, 2023)
The inhomogeneities of the metal/semiconductor (M/S) interface have been investigated for many decades and several models have been proposed to explain the physics of the interface state in such contacts. Two important and famous approaches are cited in this chapter book explaining the physics behind the metal/semiconductor (Schottky diode) interface state: the Werner and Guttler’s model and the Tung’s model. The proposed approaches are based on the temperature dependent of the most important parameter characterizing the M/S interface: the barrier high \(φ\)B. Accordingly, the temperature effect on the other parameters, that characterize the current-voltage measurements like the mean barrier high \(φ^-\)B0, the standard deviation \(σ\)s, the voltage coefficients \(ρ\)2 and \(ρ\)3 for the barrier high and the standard deviation respectively, and the series resistance Rs, is also approving the evidence the inhomogeneity of the interface between the metal and the semiconductor. In the light of this concept, a deep analysis is made on the state of the Mo/n-type-4H-SiC Schottky diode in the range of temperature (298-498) K via its current-voltage measurements. The analysis is based on the simultaneous extraction of the parameters (`\(φ^-\)B0,\(ρ\)2, \(ρ\)3, \(σ\)s, Rs) that define the current-voltage measurements as function of temperature by using the vertical optimization method (VOM). In order to explain the obtained results, we have used the Werner and Guttler’s model to approve the inhomogeneity of the Mo/4H-SiC interface in the studied range of temperature. The investigations reported in this book chapter for the Mo/n-type4H-SiC contact confirm the existence of an inhomogeneous interface by the use of the Werner and Guttler’s approach.